Self-adhesive cling film and preparation method thereof
By using modified silica and modified POE elastomers in PE plastic wrap, the problem of poor breathability and oxidation resistance of PE plastic wrap is solved, and higher breathability and oxidation resistance are achieved, and freshness is extended The service life of the membrane and reduces the risk of environmental pollution.
Patent Information
- Application Number
- CN202311166430.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The breathable and antioxidant properties of PE plastic wrap are poor, resulting in a degradation in performance during heating or long-term use, and traditional antioxidants are prone to volatile and pollute the environment.
Using modified silica and modified POE elastomers, tea saponins are grafted during the preparation of modified silica to enhance antioxidant and antibacterial properties, and improve compatibility and mechanics by modifying POE elastomers. performance.
It improves the breathability and antioxidant properties of plastic wrap, extends the service life of plastic wrap, reduces dependence on traditional antioxidants, and reduces the risk of environmental pollution.
Smart Images

Figure BDA0004442461120000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cling film, and in particular relates to a self-adhesive cling film and a preparation method thereof. Background Art
[0002] PE cling film, as a common plastic film for food preservation and packaging, has many advantages, but also has the following disadvantages: PE cling film usually has low air permeability, which means that some foods may need to be kept dry when wrapped to prevent moisture accumulation, and some foods may require materials with higher air permeability to maintain their quality; and cling film made of PE often undergoes oxidative decomposition when heated or used for a long time, resulting in a decrease in the performance of the cling film and a loss of ductility, transparency and sealing properties.
[0003] At present, antioxidants are mainly added to avoid or inhibit the occurrence of this aging phenomenon. However, traditional antioxidants have a small relative molecular mass and are easy to volatilize and migrate from the rubber matrix, which not only reduces its anti-thermal oxidative aging performance, but also pollutes the environment. Summary of the invention
[0004] The purpose of the present invention is to provide a self-adhesive cling film and a preparation method thereof, so as to solve the problems of poor air permeability and poor antioxidant performance of PE cling film.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A self-adhesive cling film, comprising the following raw materials in parts by weight:
[0007] Linear low density polyethylene: 100-120 parts;
[0008] Ultra-low density polyethylene: 8-10 parts;
[0009] Modified POE elastomer: 25-35 parts;
[0010] Modified silica: 5-10 parts;
[0011] Glycerol: 1-3 parts;
[0012] Sorbitol: 2-4 parts;
[0013] Trimethylolpropane: 0.5-1 part;
[0014] Wherein, the modified silicon dioxide is prepared by the following steps:
[0015] Add amino-functionalized silica and tea saponin to toluene, ultrasonically disperse for 30 minutes, stir evenly, heat to 40°C, add triethylamine, protect with nitrogen, react for 4.5 hours, cool to room temperature, wash 3 times with anhydrous toluene, filter, put into a vacuum oven at 80°C and dry for 24 hours to obtain modified silica.
[0016] Furthermore, the usage ratio of amino-functionalized silica, tea sapogenin, toluene and triethylamine is 8 g:3 g:150 mL:0.3 g.
[0017] Further, amino-functionalized silica is prepared by the following steps:
[0018] Add nano-silica to an ethanol / water mixed solution, ultrasonically disperse, adjust the pH to 4 with hydrochloric acid solution, add silane coupling agent KH550, ultrasonically disperse, heat to 80°C and stir for 10 hours, cool to room temperature, wash with ethanol three times, filter, put into a 60°C vacuum drying oven, and dry for 24 hours to obtain amino-functionalized silica.
[0019] Furthermore, the dosage ratio of nano-silica, ethanol / water mixed solution and silane coupling agent KH550 is 10g:100mL:1.5g; the volume ratio of ethanol to water in the ethanol / water mixed solution is 3:1, and the mass fraction of the hydrochloric acid solution is 37%.
[0020] Further, the modified POE elastomer is prepared by the following steps:
[0021] POE elastomer (polyolefin elastomer) was added to an internal mixer for plasticization, thin passing 3 times, stearic acid, paraffin oil, white carbon black / silane coupling agent KH550 mixture and accelerator M were added, the roller distance was adjusted, thin passing 3 times, and mixing was performed for 20 minutes to obtain a modified POE elastomer.
[0022] Furthermore, the mass ratio of POE elastomer, stearic acid, paraffin oil, white carbon black / silane coupling agent KH550 mixture and accelerator M is 100:6:25:20-30:1.5; wherein the amount of silane coupling agent KH550 is 10% of white carbon black.
[0023] Furthermore, the initial temperature of the internal mixer is 90-95°C, the rotation speed is 70-80r / min, and the roller distance is adjusted to 2-3mm.
[0024] The present invention also provides a method for preparing a self-adhesive cling film, comprising the following steps:
[0025] Step 1: put the raw materials into the hot mixer in the extruder, heat to 90°C, stir for 30 minutes, put into the low-speed cold mixer, stir, cool and discharge;
[0026] Step 2: Add the mixed material into the screw extruder. The mixed material is heated, sheared, conveyed and plasticized, and finally enters the die head to be blown into a film.
[0027] Furthermore, the temperature of the screw, barrel and die head mold in the extrusion film blowing unit is 115-120°C.
[0028] Beneficial effects of the present invention:
[0029] The present invention adds modified silicon dioxide in the preparation process of PE cling film, and the modified silicon dioxide is made of amino-functional silicon dioxide grafted with tea sapogenin with antioxidant and antibacterial properties; on the one hand, tea sapogenin has a biological activity inhibitory effect on some bacteria and molds, can effectively inhibit the growth of molds in food, and has good migration resistance and thermal oxidation aging resistance, and can play an antioxidant role in the preparation process of cling film. On the other hand, the modified silicon dioxide fills the PE cling film so that the cling film has a microporous structure, and the microporous particle size is very small, only water vapor can pass through but liquid cannot pass through, thereby reducing the condensation of water vapor on the surface of the cling film and avoiding the generation of fog. In addition, the addition of silicon dioxide helps to improve the mechanical properties of the blending system and further improves the toughness of the food cling film.
[0030] In the modified POE elastomer of the present invention, the ethoxyl group on the silane coupling agent KH550 reacts with the surface hydroxyl group of white carbon black, thereby improving the compatibility between white carbon black and the POE elastomer; and KH550 can play a bridging role between rubber macromolecules and inorganic fillers, thereby enhancing the bonding force with the rubber; when subjected to external force, the relative slippage between molecular chains is restricted, thereby reducing the compression permanent deformation of the POE elastomer and improving the rebound performance; after the modified POE is added in the preparation process of the cling film, the regularity of the PE macromolecular chain is destroyed, the PE crystallinity is reduced, the shrinkage rate is reduced, and the bonding strength is increased; and because the ethylene chain segments contained in POE and the molecular weight distribution are narrow, the compatibility with PE is good, thereby improving the toughness and viscosity of the blend.
[0031] In the preparation process of the PE cling film of the present invention, the addition of modified silicon dioxide makes it unnecessary to use an additional antioxidant during the production of the cling film, thereby greatly reducing environmental pollution, reducing production costs and being safe and non-toxic. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] This embodiment provides a modified silicon dioxide, which is prepared by the following steps:
[0035] The first step is to prepare amino-functionalized silica:
[0036] 10 g of nano-silica (particle size of 100 nm) was added to 100 mL of ethanol / water mixed solution, ultrasonically dispersed, the pH was adjusted to 4 with hydrochloric acid solution, 1.5 g of silane coupling agent KH550 was added, ultrasonically dispersed, the temperature was raised to 80°C and stirred for 10 h, cooled to room temperature, washed with ethanol 3 times, filtered, placed in a 60°C vacuum drying oven, and dried for 24 h to obtain amino-functionalized silica.
[0037] Step 2: Preparation of modified silica
[0038] Add 8 g of amino-functionalized silica and 3 g of tea saponin (purity of 95%) into 150 mL of toluene, ultrasonically disperse for 30 min, stir evenly, heat to 40°C, add 0.3 g of triethylamine, protect with nitrogen, react for 4.5 h, cool to room temperature, wash 3 times with anhydrous toluene, filter, put into a vacuum oven at 80°C and dry for 24 h to obtain modified silica.
[0039] Example 2
[0040] This embodiment provides a modified POE elastomer, which is prepared by the following steps:
[0041] 100 g of POE elastomer (model 8150, DuPont Dow, USA) was added to an internal mixer for plasticization, thinned three times, 6 g of stearic acid, 25 g of paraffin oil, 22 g of a mixture of white carbon black / silane coupling agent KH550 and 1.5 g of accelerator M were added, the roller distance was adjusted to 3 mm, thinned three times, and mixed for 20 minutes to obtain a modified POE elastomer.
[0042] Example 3
[0043] This embodiment provides a modified POE elastomer, which is prepared by the following steps:
[0044] 100 g of POE elastomer (model 8150, DuPont Dow, USA) was added to an internal mixer for plasticization, thinned three times, 6 g of stearic acid, 25 g of paraffin oil, 25 g of white carbon black / KH550 mixture and 1.5 g of accelerator M were added, the roller distance was adjusted to 3 mm, thinned three times, and mixed for 20 minutes to obtain a modified POE elastomer.
[0045] Example 4
[0046] This embodiment provides a modified POE elastomer, which is prepared by the following steps:
[0047] 100 g of POE elastomer (model 8150, DuPont Dow, USA) was added to an internal mixer for plasticization, thinned three times, 6 g of stearic acid, 25 g of paraffin oil, 29 g of white carbon black / KH550 mixture and 1.5 g of accelerator M were added, the roller distance was adjusted to 3 mm, thinned three times, and mixed for 20 minutes to obtain a modified POE elastomer.
[0048] Example 5
[0049] This embodiment provides a self-adhesive cling film and a preparation method thereof:
[0050] Weigh 110 parts of linear low-density polyethylene (model 1002KW, ExxonMobil); 8 parts of ultra-low-density polyethylene (model 4203, DuPont Dow Company, USA); 25 parts of modified POE elastomer in Example 2; 8 parts of modified silica; 2 parts of glycerol; 2 parts of sorbitol; and 0.8 parts of trimethylolpropane.
[0051] Step 1: Put linear low-density polyethylene, ultra-low-density polyethylene, modified POE elastomer, modified silica, glycerol, sorbitol and trimethylolpropane into the hot mixer in the extruder, heat to 90°C, stir for 30 minutes, put into a low-speed cold mixer, stir, cool and discharge;
[0052] Step 2: Add the mixed material into the screw extruder, and the mixed material is heated, sheared, conveyed and plasticized, and finally enters the die head and is blown into a film to obtain the PE cling film.
[0053] Example 6
[0054] Weigh 110 parts of linear low-density polyethylene (model 1002KW, ExxonMobil); 8 parts of ultra-low-density polyethylene (model 4203, DuPont Dow Company, USA); 28 parts of modified POE elastomer in Example 3; 8 parts of modified silica; 2 parts of glycerol; 2 parts of sorbitol; and 0.8 parts of trimethylolpropane.
[0055] Step 1: Put linear low-density polyethylene, ultra-low-density polyethylene, the modified POE elastomer in Example 3, modified silica, glycerol, sorbitol and trimethylolpropane into a hot mixer in an extruder, heat to 90° C., stir for 30 minutes, put into a low-speed cold mixer, stir, cool and discharge;
[0056] Step 2: Add the mixed material into the screw extruder, and the mixed material is heated, sheared, conveyed and plasticized, and finally enters the die head to be blown into a film; thus, a PE cling film is obtained.
[0057] Example 7
[0058] The only difference from Example 5 is that:
[0059] Weigh 115 parts of linear low-density polyethylene, 8 parts of ultra-low-density polyethylene, 33 parts of the modified POE elastomer in Example 4, and 10 parts of modified silicon dioxide to obtain a PE cling film.
[0060] Example 8
[0061] The only difference from Example 5 is that:
[0062] Weigh 118 parts of linear low-density polyethylene, 8 parts of ultra-low-density polyethylene, 30 parts of the modified POE elastomer in Example 3, and 8 parts of modified silicon dioxide to obtain a PE cling film.
[0063] Comparative Example 1
[0064] Weigh 110 parts of linear low-density polyethylene, 8 parts of ultra-low-density polyethylene, 28 parts of the modified POE elastomer in Example 3, 8 parts of silicon dioxide (without any change), 2 parts of glycerol, 2 parts of sorbitol, and 0.8 parts of trimethylolpropane.
[0065] Step 1: Put linear low-density polyethylene, ultra-low-density polyethylene, the modified POE elastomer in Example 3, modified silica, glycerol, sorbitol and trimethylolpropane into a hot mixer in an extruder, heat to 90° C., stir for 30 minutes, put into a low-speed cold mixer, stir, cool and discharge;
[0066] Step 2: Add the mixed material into the screw extruder, and the mixed material is heated, sheared, conveyed and plasticized, and finally enters the die head to be blown into a film; thus, a PE cling film is obtained.
[0067] Comparative Example 2
[0068] The only difference from Comparative Example 1 is that:
[0069] Weigh 110 parts of linear low-density polyethylene, 8 parts of ultra-low-density polyethylene, 28 parts of POE elastomer (model 8150, DuPont Dow Company, USA), 8 parts of nano-silicon dioxide (particle size of 100 nm), 2 parts of glycerol, 2 parts of sorbitol, and 0.8 parts of trimethylolpropane to obtain a PE cling film.
[0070] Performance tests were performed on Examples 5-8 and Comparative Examples 1-2:
[0071] Mechanical test: The length of the long strip specimen is 10mmx150mm, the average thickness is 0.8mm, and the test is carried out in accordance with GB / T13022-1991 standard.
[0072] Tear strength test: Tested in accordance with QB / T1130-1991 standard.
[0073] Air permeability and moisture permeability test: The specimen diameter is 75mm, three in each group, and three groups are tested, respectively according to GB / T1038-2000 and GB / T1037-2021 standards.
[0074] Shrinkage test: Wrap in a shallow dish with plastic wrap and place in a refrigerator at 3-5℃ for 8 hours. Observe the tightness of the film on the surface of the dish. If it is tight and smooth, it is excellent. If it is not tight and has a little ripples, it is fair.
[0075] Adhesion test: Wrap in a shallow dish with plastic wrap and place in a refrigerator at 3-5℃ for 8 hours to observe whether the bottom is loose. If the bottom is not loose and has good adhesion, it is judged as excellent; if it is loose, it is judged as poor.
[0076] Antioxidant performance test: 0.02 mg / mL 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) solution was prepared with anhydrous ethanol; the sample was punched into a disc with a diameter of 10 mm, and 10 mL of DPPH solution was added to the sample discs respectively. After magnetic stirring at room temperature for 30 minutes, the clear liquid was taken to measure the absorbance at 517 nm.
[0077] The test results are shown in Table 1:
[0078] Table 1
[0079]
[0080] It can be seen from Table 1 that, compared with Comparative Examples 1-2, the results of tensile strength, elongation at break and tear strength in Examples 5-8 are better, indicating that the cling film prepared by the present invention has better mechanical effect; it can be seen from the data of oxygen permeability and moisture permeability in the table that the cling film prepared by the present invention has excellent air permeability, and has higher adhesion and retraction; according to the DPPH free radical scavenging rate in the table, it can be seen that the prepared cling film has excellent antioxidant properties.
[0081] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A self-adhesive cling film, characterized in that: By weight, it includes the following raw materials: Linear low density polyethylene: 100-120 parts; Ultra-low density polyethylene: 8-10 parts; Modified POE elastomer: 25-35 parts; Modified silica: 5-10 parts; Glycerol: 1-3 parts; Sorbitol: 2-4 parts; Trimethylolpropane: 0.5-1 part; Wherein, the modified silicon dioxide is prepared by the following steps: Add amino-functionalized silica and tea saponin into toluene, disperse by ultrasonication for 30 minutes, stir evenly, heat to 40°C, add triethylamine, protect with nitrogen, react for 4.5 hours, cool to room temperature, wash, filter, dry in a vacuum oven at 80°C for 24 hours, and obtain modified silica; Wherein, the modified POE elastomer is prepared by the following steps: The POE elastomer was added into an internal mixer for plasticization, thin passing 3 times, stearic acid, paraffin oil, white carbon black / silane coupling agent KH550 mixture and accelerator M were added, the roller distance was adjusted, thin passing 3 times, and mixing was performed for 20 minutes to obtain a modified POE elastomer.
2. A self-adhesive cling film according to claim 1, characterized in that: The dosage ratio of amino-functionalized silica, tea saponin, toluene and triethylamine is 8g:3g:150mL:0.3g.
3. A self-adhesive cling film according to claim 1, characterized in that: Amino-functionalized silica was prepared by the following steps: Add nano-silica to an ethanol / water mixed solution, disperse it ultrasonically, adjust the pH to 4 with hydrochloric acid solution, add silane coupling agent KH550, disperse it ultrasonically, heat it to 80°C and stir it for 10 hours, cool it to room temperature, wash it, filter it, put it into a vacuum drying oven at 60°C, and dry it for 24 hours to obtain amino-functionalized silica.
4. A self-adhesive cling film according to claim 3, characterized in that: The dosage ratio of nano-silica, ethanol / water mixed solution and silane coupling agent KH550 is 10g:100mL:1.5g; the volume ratio of ethanol to water in the ethanol / water mixed solution is 3:1, and the mass fraction of the hydrochloric acid solution is 37%.
5. The self-adhesive cling film according to claim 1, characterized in that: The mass ratio of POE elastomer, stearic acid, paraffin oil, white carbon black / silane coupling agent KH550 mixture and accelerator M is 100:6:25:20-30:1.5; the amount of silane coupling agent KH550 is 10% of white carbon black.
6. The self-adhesive cling film according to claim 1, characterized in that: The initial temperature of the internal mixer is 90-95°C, the speed is 70-80r / min, and the roller distance is adjusted to 2-3mm.
7. The method for preparing a self-adhesive cling film according to claim 1, characterized in that: The steps include: Step 1: put the raw materials into the hot mixer in the extruder, heat to 90°C, stir for 30 minutes, put into the low-speed cold mixer, stir, cool and discharge; Step 2: Add the mixed material into the screw extruder. The mixed material is heated, sheared, conveyed and plasticized, and finally enters the die head to be blown into a film.
8. The method for preparing a self-adhesive cling film according to claim 7, characterized in that: The temperature of the screw, barrel and die head in the extrusion film blowing unit is 115-120℃.
Citation Information
Patent Citations
PE (Poly Ethylene) preservative film and preparation method thereof
CN103450547A
Anti-static degradable film and preparation method thereof
CN112793274A
Preparation method and application of high-antibacterial degradable nano cellulose film
CN116478440A